The Syrian "Other" in everyday life: Perspectives on Syrian refugees in Üsküdar - Dursun, Nurbanu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
This thesis explores mobilization of conservative people for the refugee issue in the everyday life of Üsküdar and how they perceive the Syrian refugees arriving Turkey since the early days of the Syrian Civil War that started in 2011. In order to explore how people mobilize for the refugee issue, this thesis relies on a field study composed of in-depth interviews with and participant observation of people mobilized for the refugee issue in Üsküdar as an exemplary case. It relies on a merging of two theoretical outlooks, discourse analysis and sensory ethnography in order, to analyze the data. The study argues that the refugee issue is a privatized area in Turkey and that the neoliberal state in Turkey is getting less accountable for the refugee issue.!This shifts the responsibility for addressing refugee issues to local communities, who then have to mobilize. This mobilization relies on neo-Ottomanist discourses and nostalgia. Therefore, the study argues that there is a contingent and collaborative relationship between neoliberalism and neo-Ottomanism on the refugee issue in Turkey. Although neo-Ottomanism is not a recent phenomenon, the thesis explores how the political discourse of neo-Ottomanism acquires hegemony over and gets internalized by the society. In that sense, there are reevaluations of three important key areas: the recent past through the Bosnian War, the imaginary on the West and Kemalism. These areas produce and reproduce new subjectivities and collectivities in a neoliberal state and society in accordance with neo-Ottomanism. This thesis emphasizes the transformative character of migrations in everyday life by presenting the local perspectives.
Keywords: Refugees -- Syria.; Refugees, Syrian -- Turkey -- Üsküdar.